THE INFLUENCE OF THE CONTENT AND ESSENCE ON THE TRANSLATION OF THE WORKS OF ALBER CAMUS (Scientific journal of the Fergana State University, 2024)
The purpose of this article is to discuss specific problems of translating works from one language to another on a scientific basis. The article analyzes the strengthening of ties between national literatures with the help of translators, the processes of interaction and mutual enrichment. Today, with the help of translators, ties between national literatures are strengthened, the processes of interaction and mutual enrichment are accelerated. It should be noted here that interest in French culture, language and literature in Uzbekistan has always been great. In particular, it is noted that the importance of translating famous and famous works of French literature into Russian from the original version into the Uzbek language has increased significantly. At the moment, skillfully translating the spirit of Camus's original works, especially the language, into Uzbek is very difficult and requires a lot of work. In addition, in the article, the study of the translation of a work of fiction and its comparison with the original version is intended not only to determine the harmony between the universal, spiritual and cultural values ​​of the peoples of the world, but also to study the national and cultural characteristics of each language. This is justified by the fact that it serves for the interpretation and reception of the work. If the translation of Camus’s works is not at the level of the original, then the translation hinders the understanding of the French writer’s existentialist ideas about the will and strength of man, the integrity of man and nature, and the correct perception of the essence of the world. the absurd content that the author wants to offer. Therefore, the artistic technique implemented through translation is important for the correct interpretation of the main idea of the work and the artistic intention of the author.